Workshop Soft Skills Customer Service untuk Siswa SMK Perkantoran PAB 3 Medan Estate - Sharina Amanda; Handayani, Cici; Hastuty, Widy; Sipayung, Tumini; Tarigan, Nirwaty; Harizahayu (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to enhance soft skills in customer service for students of SMK Perkantoran (Office Vocational School) PAB 3 Medan Estate. Soft skills are as important as skills in communication skills, empathy, service ethics, and emotional management are essential competencies for prospective administrative office workers. There are interactive workshops, group discussions, and customer service simulations as part of this community service activity. In this event, it can be found that participants demonstrated improved understanding and practical skills in customer interactions. This activity is expected to positively contribute to the students' readiness to enter the workforce